Deserto azul - Santos, Eder; Cerqueira, Mônica; Esteves, Odilon, 1978-; Mendonça, María Luisa, 1970-; Diaz, Chico, 1959- (Trem Chic, 2014)
In a age where religiosity, sports, memory or truthfulness are no longer in use, encountering no longer happens in physical presence. He is seeking for elevation of consciousness by following his dreams and intuitions. Revelations made through mysterious symbols take him to an evolutive path thru an enigmatic meeting with his soul mate. His journey through the Blue Desert reveals the opportunity to understand the purpose of life and the meaning of human existence.--